A matrix converter based voltage regulator for MV rural feeders - Ali, S.; Wolfs, Peter (2014)
© 2014 IEEE. In this paper a Matrix Converter (MC) has been used with a series voltage injection transformer to regulate the voltages on a Medium-Voltage (MV) rural distribution feeder. This approach is well suited to pole top regulator applications as DC bus capacitors are avoided. The MC is controlled using a Space Vector Modulation (SVM) method that is capable of regulating the positive-sequence voltage on a feeder while simultaneously cancelling negative sequence voltages produced by high levels of load or distributed generation unbalance or by the use of non-transposed lines. The study of the MC modulation processes is undertaken with an exact switching model for the higher frequency behaviours of the converter while a small signal Instantaneous Reactive Power (IRP) based average signal model is used to study the multi-cycle dynamic regulatory performances.